2011
DOI: 10.5586/asbp.2007.036
|View full text |Cite
|
Sign up to set email alerts
|

Low level of genetic variation within Melica transsilvanica populations from the Kraków-Częstochowa Upland and the Pieniny Mts revealed by AFLPs analysis

Abstract: Fragmented distribution, the breeding system and effects of genetic drift in small-size populations occurring at edge of the species range play an important role in shaping genetic diversity of such a species. Melica transsilvanica is a plant rare in the flora of Poland, where it reaches the northern limit of its continuous range. Amplified Fragment Length Polymorphism (AFLP) DNA profiling method was applied to measure genetic diversity among and within populations of M. transsilvanica. Additionally, genetic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Resuming findings from the previous papers [24,[43][44][45][46][47][48][49]51,79], own fieldworks conducted in 2005-2011 and currently displayed evidences based on AFLP fingerprinting and morphological data, we can state that M. ciliata L. does not occur in the Polish flora. On the contrary, a detailed analysis of the AFLP band patterns of Sudetian "M. ciliata" clearly showed its genetic identity with M. transsilvanica Schur (see "Results").…”
Section: Taxonomic Status Of 'Melica Ciliata' In Polandmentioning
confidence: 89%
See 1 more Smart Citation
“…Resuming findings from the previous papers [24,[43][44][45][46][47][48][49]51,79], own fieldworks conducted in 2005-2011 and currently displayed evidences based on AFLP fingerprinting and morphological data, we can state that M. ciliata L. does not occur in the Polish flora. On the contrary, a detailed analysis of the AFLP band patterns of Sudetian "M. ciliata" clearly showed its genetic identity with M. transsilvanica Schur (see "Results").…”
Section: Taxonomic Status Of 'Melica Ciliata' In Polandmentioning
confidence: 89%
“…Additionally, both species are able to hybridize in natural habitats that can blur inter-specific morphological differences [42]. However, the previous genetic analyses showed that these species are clearly genetically distinct [43,44]. Thus, we were interested in determining whether combined molecular and morphological data would be effective in distinguishing M. ciliata and M. transsilvanica.…”
Section: Studies On Melica Ciliata/m Transsilvanica In Polandmentioning
confidence: 99%
“…The high level of among-population diversity was linked with a decreased within-population diversity index ( PLP 3.7%) and nearly total genetic homogeneity. Taken together, the results of the studies on M. transsylvanica in the Pieniny Mts point to the high geographical isolation of the metapopulation in the region and the dominant self-pollinating system of the species is inducing the lack of gene flow 58 .…”
Section: Discussionmentioning
confidence: 86%
“…A much higher among-population component of diversity (AMOVA) that amounted to 86% displayed a grass, Melica transsilvanica , studied in the Pieniny Mts and Małopolska Upland (southern Poland) 58 . The species has a different ecological profile than G. imbricatus ; it grows on dry, exposed outcrops in pioneer rupicolous grasslands ( Seslerio-Festucion duriusculae alliance in the Pieniny Mts) and in xerothermic grasslands of the Cirsio-Brachypodion pinnati alliance on the Małopolska Upland.…”
Section: Discussionmentioning
confidence: 99%
“…In the M. ciliata complex, low genetic diversity within populations and high differentiation among them were determined (Tyler, 2004;Szczepaniak & Cieślak, 2006, 2007, 2009, and this is confirmed here by high F ST values (Table S2). Consequently, facultative apomixis or even a predominantly autogamous reproduction mode has been suggested for the M. ciliata complex (Tyler, 2004;Szczepaniak & Cieślak, 2007), the latter also supported by features in floral structures, that is, spikelets comprising one fertile floret and two or three diminished florets at the apex, small anthers, and cleistogamous flowers (Szczepaniak & Cieślak, 2007).…”
Section: Genetic and Morphological Consequences Of Ecological Strateg...mentioning
confidence: 99%